Successful Intratracheal Treatment of Phage and Antibiotic Combination Therapy of a Multi-Drug Resistant Pseudomonas aeruginosa Murine Model - Christopher Duplessis; Jonathan M. Warawa; Matthew B. Lawrenz; Matthew Henry; Biswajit Biswas (MDPI AG, 2021)
Background: Pseudomonas aeruginosa (PsA) is a common etiology of bacteria-mediated lower respiratory tract infections, including pneumonia, hospital acquired pneumonia (HAP), and ventilator-associated pneumonia (VAP). Given the paucity of novel antibiotics in our foreseeable pipeline, developing novel non-antibiotic antimicrobial therapies saliently targeting drug resistant PsA isolates remains a priority. Lytic bacteriophages (or phages) have come under scrutiny as a potential antimicrobial for refractory bacterial infections. We evaluated intratracheally and intraperitoneally (IP) administered phage therapy (with/without meropenem) in an acute immunocompromised mouse model of multi-drug resistant (MDR) PsA pulmonary infection. The MDR P. aeruginosa respiratory disease model used in these studies was developed to investigate novel therapies that might have efficacy as either monotherapies or as combination therapy with meropenem. Methods: We utilized eight-week-old, 18 g BALB/cJ female mice and an MDR strain of PsA (UNC-D). Mice were immunosuppressed with cyclophosphamide. We employed a three-phage cocktail targeting PsA (PaAH2ΦP (103), PaBAP5Φ2 (130), and PaΦ (134)), confirmed to exhibit in vitro suppression of the infecting isolate out to 45 h. Suppression was confirmed with phages acting in isolation and in combination with meropenem. Results: IP administration of phage did not protect mice from death. A one-time delivery of phage directly to the lungs via a single intubation-mediated, intratracheal (IMIT) instillation protected mice from lethal infection. Protection was observed despite delaying therapy out to 6 h. Finally, we observed that, by slowing the progression of infection by treatment with a sub-efficacious dose of meropenem, we could protect the mice from lethal infection via IP phage administration coupled to meropenem, observing partial additive effects of phage-antibiotic combination therapy. Conclusions: A personalized phage cocktail administered via IMIT exhibits high therapeutic efficacy, despite delayed treatment of 6 h in a lethal MDR PsA pneumonia model. IP phage alone did not forestall mortality, but exhibited efficacy when combined with meropenem and IMIT-administered phage. These additive effects of combined IP phage and meropenem confirm that phage may indeed reach the lung bed via the systemic circulation and protect mice if the infection is not too acute. Therefore, adjunctive phage therapy with concerted attention to identifying optimal phage targeting of the infecting isolate in vitro may exhibit transformative potential for combating the specter of MDR bacterial infections. Phage should serve as an integral component of a four-pronged approach coupled with antibiotics, source control, and immune optimization.